Oral Tranexamic Acid with Fluocinolone-Based Triple Combination Cream Versus Fluocinolone-Based Triple Combination Cream Alone in Melasma: An Open Labeled Randomized Comparative Trial - Padhi, Tanmay (Indian J Dermatol, 2015)
BACKGROUND: Melasma is a common acquired cause of facial hyperpigmentation with no definitive therapy. Tranexamic acid, a plasmin inhibitor, has demonstrated depigmenting properties and combining this oral drug with other modalities of treatment has shown promising results. OBJECTIVES: To compare the efficacy of a combination of oral tranexamic acid and fluocinolone-based triple combination cream with that of fluocinolone-based triple combination cream alone in melasma among Indian patients. MATERIALS AND METHODS: 40 patients of melasma of either sex attending to dermatology OPD were enrolled in this study. Participants were randomly divided into two groups with 20 patients in each group. Group A patients were asked to apply the cream only and Group B patients received oral tranexamic acid 250 mg twice daily and applied a triple combination cream containing fluocinolone acetonide 0.01%, tretinoin 0.05%, and hydroquinone 2% once daily for 8 weeks. Response was evaluated using melasma area severity index (MASI) at baseline, 4 weeks, and 8 weeks. RESULTS: 40 patients completed the study. The MASI scores at baseline, 4 weeks and 8 weeks in group A were 15.425 + 1.09, 11.075 + 9.167 and 6.995 + 6.056 respectively and in group B 18.243 + 1.05, 6.135 + 4.94 and 2.19 + 3.38. Intergroup comparison showed a faster reduction in pigmentation in Group B as compared to Group A and the results were statistically significant at 4 weeks (P value 0.014) and 8 weeks (P value 0.000). The efficacy was maintained throughout the 6-month follow-up period. CONCLUSION: Addition of oral tranexamic acid to fluocinolone-based triple combination cream results in a faster and sustained improvement in the treatment of melasma.